ANALISIS PENGARUH PELATIHAN ROBOT LINE FOLLOWER DAN LAMPU IOT DALAM MENINGKATKAN MINAT STEM SISWA SMA - Junita, Junita; Uranus, Henri P.; Kanalebe, Herman; A.R, M. Gracio; Pardede, Marincan; Mangunsong, Rianto; Yulian, Dwi Heri; Prafo, Salfatore Yan; Susanto, Kathleen Gabriella; Yapply, Legolas (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2024)
This analysis aims to compare the effectiveness of two Community Service (PkM) activities in increasing high school students' interest in STEM (Science, Technology, Engineering, and Mathematics). The activities compared include line follower robot training and IoT (Internet of Things) light-making training. Both activities were designed to provide practical understanding and hands-on experience for students in the field of technology and engineering. This study used an experimental method by comparing students' perceptions of STEM before and after the training. The results of this analysis show that IoT light training was overall more effective in increasing students' interest in the Electrical Engineering program, with a positive perception increase of 58% in the